From “cracking the orthographic code” to “playing with language”: toward a usage-based foundation of the reading process - Wallot, Sebastian (Frontiers in Psychology, 2014)
The empirical study of reading dates back more than 125 years. But despite this long tradition, the scientific understanding of reading has made rather heterogeneous progress: Many factors that influence the process of text reading have been uncovered, but theoretical explanations remain fragmented; no general theory pulls together the diverse findings. A handful of scholars have noted that properties thought to be at the core of the reading process do not actually generalize across different languages or form situations single-word reading to connected text reading. Such observations cast doubt on many of the traditional conceptions about reading. In this article, I suggest that the observed heterogeneity in the research is due to misguided conceptions about the reading process. Particularly problematic are the unrefined notions about meaning which undergird many reading theories: Most psychological theories of reading implicitly assume a kind of elemental token semantics, where words serve as stable units of meaning in a text. This conception of meaning creates major conceptual problems. As an alternative, I argue that reading shoud be rather understood as a form of language use, which circumvents many of the conceptual problems and connects reading to a wider range of linguistic communication. Finally, drawing from Wittgenstein, the concept of ‘language games’ is outlined as an approach to language use that can be operationalized scientifically to provide a new foundation for reading research.